Sustainable intensification of rice-based systems with potato in eastern indo-gangetic plains - Gatto, M.; Petsakos, Athanasios; Hareau, Guy (Springer, 2020)
In many parts of Asia food security and poverty remain issues even though arable land is available to produce nutritious food. Sustainable intensification of agricultural systems has been proposed to produce more outputs on same land area whilst minimizing environmental degradation. Tradeoffs, however, are inevitable and evidence thereof is scant. In this study, we analyze effects of sustainable intensification of rice-based systems with potato and focus on the Eastern Indo-Gangetic Plains of India and Bangladesh. A literature review, expert consultation, and an economic surplus exercise are used to address our objective. We find that sustainable intensification has a huge potential and positive welfare effects. Socio-economic tradeoffs, especially for labour, need to be considered and balanced out. Increasing input efficiency for instance by improving farming practices may reduce negative environmental effects.